DEVELOPMENT OF METHODICS FOR THE CREATION ON ITS BASIS OF A SYSTEM FOR AUTOMATICALLY COMBINING INTERNATIONAL NEWS - M. I. Ivashchenko; N. N. Gorlushkina; V. N. Stromtsova; M. V. Guseva (Современная наука и инновации)
The article deals with the problem of combining international multilingual news on the common themes. The relevance of the topic is based on the need for prompt analysis of the news information in various spheres. It was hypothesized that combining international multilingual news with the application of an automatic system would ensure accuracy and completeness of the compilation of up to 75% if the basis of this system was provided as a methodology based on clustering and tokenization methods. The goal of the research is the development of the methodology for the automatic combination of international news information for optimizing its presentation to the consumer.